2019
DOI: 10.3390/ani9121108
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Fucoidan against Hydrogen Peroxide-Induced Oxidative Damage in Porcine Intestinal Epithelial Cells

Abstract: This study was conducted to evaluate the effectiveness of fucoidan in ameliorating hydrogen peroxide (H2O2)-induced oxidative stress to porcine intestinal epithelial cell line (IPEC-1). The cell viability test was initially performed to screen out appropriate concentrations of H2O2 and fucoidan. After that, cells were exposed to H2O2 in the presence or absence of pre-incubation with fucoidan. Hydrogen peroxide increased the apoptotic and necrotic rate, boosted reactive oxygen species (ROS) generation, and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…These findings suggest that all the polysaccharide samples are able to inhibit intracellular H 2 O 2 ‐induced ROS production and between fucoidans, those extracted with UM showed the highest ROS scavenging activity. Similar to our results, Li et al (2019) reported that pre‐incubation with commercial fucoidan (extracted from Undaria pinnatifida , Sigma‐Aldrich, St. Louis, MO, USA) inhibited the ROS accumulation in H 2 O 2 ‐treated IPEC‐1 cells. In another study, fucoidan extracted from Ecklonia cava significantly decreased the intracellular ROS contents in H 2 O 2 ‐induced PC‐12 and MC‐IXC cells (Park et al, 2018).…”
Section: Resultssupporting
confidence: 92%
“…These findings suggest that all the polysaccharide samples are able to inhibit intracellular H 2 O 2 ‐induced ROS production and between fucoidans, those extracted with UM showed the highest ROS scavenging activity. Similar to our results, Li et al (2019) reported that pre‐incubation with commercial fucoidan (extracted from Undaria pinnatifida , Sigma‐Aldrich, St. Louis, MO, USA) inhibited the ROS accumulation in H 2 O 2 ‐treated IPEC‐1 cells. In another study, fucoidan extracted from Ecklonia cava significantly decreased the intracellular ROS contents in H 2 O 2 ‐induced PC‐12 and MC‐IXC cells (Park et al, 2018).…”
Section: Resultssupporting
confidence: 92%
“…The results reported by Li et al (2019) and are useful for future studies, as there is limited literature available regarding the effect of fucoidans on NRF2 signal transduction in the anti-inflammatory process [79].…”
Section: Keap1/nrf2 Stimulation Properties Reported From Fucoidansmentioning
confidence: 86%
“…Furthermore, the authors also described the potential of fucoidans to induce antioxidant proteins, such as HO-1 and SOD, using Western blot analysis [78]. Recently, Li et al (2019) reported that fucoidan treatment can enhance NRF2 translocation from the cytosol to the nucleus as well as NRF2 expression in hydrogen peroxide-induced oxidative damage in porcine intestinal epithelial cells. In addition, reported the NRF2 stimulatory properties of fucoidans in an ICR mouse model and HL-7702 cells.…”
Section: Keap1/nrf2 Stimulation Properties Reported From Fucoidansmentioning
confidence: 99%
“…BSP modulates intestinal epithelial cells by preserving cellular antioxidant status and promoting cytokine production. Fucoidan from Undaria pinnatifida protected porcine intestinal epithelial cells IPEC‐1 against hydrogen peroxide (H 2 O 2 )‐induced oxidative damage, which might help develop appropriate strategies for maintaining the intestinal health of young piglets (Y. Li et al., 2019). H 2 O 2 , a source of reactive oxygen species (ROS), rapidly penetrated the cell membrane and generated highly toxic hydroxyl radicals by reacting with intracellular transition metals.…”
Section: Effects Of Bsp On the Intestinal Barriermentioning
confidence: 99%